PENGEMBANGAN ASESMEN HASIL BELAJAR PENJASORKES SISWA SMA PADA PERMAINAN BOLAVOLI - Guntur, Guntur; Sukadiyanto, Sukadiyanto; Mardapi, Djemari (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2014)
Penelitian ini bertujuan menghasilkan instrumen asesmen yang valid dan reliabel untuk mengukur hasil belajar pendidikan jasmani olahraga dan kesehatan siswa SMA pada permainan bolavoli. Penelitian pengembangan mengadopsi penelitian pengembangan Borg and Gall dengan 10 langkah. Uji coba skala kecil dilakukan pada siswa Sekolah Laboratorium Olahraga FIK UNY yang berjumlah 24 anak dan uji coba skala besar pada siswa SMAN 1 Yogyakarta, SMAN 2 Wates, SMAN 1 Seyegan, SMAN 1 Sewon, dan SMAN 1 Tanjung Sari berjumlah 120 anak. Instrumen pengumpul data berupa pedoman observasi, sedangkan analisis data dengan menggunakan analisis diskriptif. Hasil penelitian ini adalah instrumen pengamatan hasil belajar siswa penjasorkes pada permainan bolavoli yang memiliki indikator, deskripsi, rubrik, prosedur asesmen. Validitas isi berdasarkan expert judgement termasuk kategori baik dan reliabilitas interrater dengan paket program Genova menghasilkan koefisen sebesar 0,82, dan Cohen's Kappa sebesar 0,79. Kesimpulan penelitian berdasarkan pendapat para guru ialah instrumen ini dapat digunakan untuk mengukur hasil belajar penjasorkes siswa SMA pada permainan bolavoli.Kata kunci: asesmen hasil belajar, pendidikan jasmani olahraga dan kesehatan, permainan bolavoli______________________________________________________________DEVELOPING THE ASSESSMENT OF LEARNING OUTCOMES FOR THE STUDENT OF PHYSICAL, SPORTS, AND HEALTH EDUCATION IN VOLLEYBALL GAME FOR SENIOR HIGH SCHOOLSAbtract This study aims to produce valid and reliable assessment instruments and to measure the learning outcomes for the students of physical, sport and health education in volleyball game for senior high schools. The research and development model chosen was the model developed by Borg & Gall, with a procedure consisting of ten stages. The field test sample consisted of the 24 students of the sports laboratory school for volleyball of the Faculty of Sports Science, Yogyakarta State University and the large-scale tests were on students of SMAN 1 Yogyakarta, Wates SMAN 2, SMAN 1 Seyegan, SMAN 1 Sewon, and SMAN 1 Tanjung Sari totaling 120 students. The instrument to collect data was observation sheet, whereas data analysis used descriptive analysis. The result of the study is an instrument for assessing the learning outcomes of physical, sports, and health education for the volleyball game that includes indicators, descriptions, and rubrics of performances, and the content validity game based on expert judgment which is good based on expert judgment; Reliability coefficient of the instrument for assessing the practice of the volleyball game by means of the Genova package program is 0.82 and that by means of Cohen's Kappa is 0.79, both satisfy the reliability requirements. Based on the the teachers' opinions, these instruments can be used to measure student learning outcomes of physical, sport and health education at volleyball game in high schools.Keywords: assessment of learning outcomes, physical sports and health education, volleyball game